Trust in God and/or Science?: Sociodemographic Differences in the Effects of Beliefs in an Engaged God and Mistrust of the COVID-19 Vaccine - Upenieks, Laura (Journal of religion and health, 2022)
At present, COVID-19 vaccines are widely available in the USA, but large proportions of the American populace remain unvaccinated. One possible source of COVID-19 vaccine hesitancy is a lack of trust in science. In this study, drawing from the large literature at the intersection of science and religion, we ask whether beliefs in an engaged God (the belief that God is involved in daily human affairs) predict mistrust of the COVID-19 vaccine and whether any observed association differs across race, gender, and education. Using nationally representative data from Wave 6 of the Baylor Religion Survey (2021), our results suggest that beliefs in an engaged God were associated with greater mistrust in the COVID-19 vaccine. This association was amplified for Hispanic and lower educated Americans. We argue that beliefs in an engaged God may promote a distrust of science, reduce motivation to get vaccinated, and derive comfort and strength by placing control over one’s life in the hands of a loving, involved deity. We also situate our findings within an emerging body of work on the "dark side" of religion and reflect on their implications for understanding the broader religion/health connection.